2015
DOI: 10.1128/aac.04140-14
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymefloquine, the Major Metabolite of the Antimalarial Drug Mefloquine, Induces Drug-Metabolizing Enzyme and Transporter Expression by Activation of Pregnane X Receptor

Abstract: f Malaria patients are frequently coinfected with HIV and mycobacteria causing tuberculosis, which increases the use of coadministered drugs and thereby enhances the risk of pharmacokinetic drug-drug interactions. Activation of the pregnane X receptor (PXR) by xenobiotics, which include many drugs, induces drug metabolism and transport, thereby resulting in possible attenuation or loss of the therapeutic responses to the drugs being coadministered. While several artemisinin-type antimalarial drugs have been sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 38 publications
(60 reference statements)
0
11
0
Order By: Relevance
“…The half-life for carboxymefloquine of 21 days [ 35 ] corresponds to the doubling time of SMX of 19 days, suggesting that the presence of the carboxymefloquine metabolite may influence SMX metabolism. A recent study has shown that the major metabolite of MQ, carboxymefloquine induces the expression of drug metabolizing enzymes and transporters by activating the pregnane X receptor [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The half-life for carboxymefloquine of 21 days [ 35 ] corresponds to the doubling time of SMX of 19 days, suggesting that the presence of the carboxymefloquine metabolite may influence SMX metabolism. A recent study has shown that the major metabolite of MQ, carboxymefloquine induces the expression of drug metabolizing enzymes and transporters by activating the pregnane X receptor [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eukaryotic expression plasmids encoding full-length human nuclear receptors PXR (Geick et al, 2001), constitutive androstane receptor (CAR) 1 (Burk et al 2002) and CAR3 (Arnold et al 2004), thyroid hormone receptor (THR) α1, THRβ1, vitamin D receptor (VDR) (Burk et al, 2005), liver X receptor (LXR) α and LXRβ (Piedade et al 2015) have all been described. Expression plasmids encoding the human small PXR variant, which consists of the ligand binding domain (amino acids 113-434) only (Jeske et al, 2017), and PXR mutant S208W/S247W/C284W (Burk et al, 2018) have already been described.…”
Section: Plasmidsmentioning
confidence: 99%
“…Structurally similar metabolites have been shown to possess similar or lower potency of induction (Petzer et al, 2003;Medina-Diaz et al, 2009). One recent report highlighted carboxymefloquine as being a pregnane X receptor (PXR) ligand, whereas the parent mefloquine was not (Piedade et al, 2015). With deleobuvir, reduction of an alkene to form CD 6168 resulted in a potent inducer.…”
Section: Tablementioning
confidence: 99%